تطبيق نظام التأمين على الودائع في العراق ودوره في سلامة أداء المصارف التجارية - علي حسين زاير; نهاد عبد الكريم العبيدي (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: ركز البحث على تحليل مدى تأثير إنشاء نظام تأمين الودائع على استق ا رر الجهاز المصرفي من خلال مناقشته واستع ا رض ملامحه وقضاياه الرئيسية، ولكون المصارف التجارية الع ا رقية وبشكل عام لا تستثمر ودائعها (رغم محدوديتها) بشكل فعال حيث يظهر وجود أموال مجمدة لا تستثمرها المصارف كما ان المصارف التجارية ولاسيما الخاصة منها تتسم بصغر حجمها وغير كافية لمنح الائتمان كقروض وسلف للمساهمة في التنمية الاقتصادية، وهذا ا رجع لأحجام المودعين عن ايداع مدخ ا رتهم في الجهاز المصرفي الع ا رقي لذلك اوضح البحث اسباب هذا الاحجام وسعى للتعرف على الاسباب الحقيقية التي ادت الى عزوف المودعين عن ايداع مدخ ا رتهم في المصارف الحكومية والخاصة في المناطق التي تنتشر فيها فروع لتلك المصارف، وتنامي ظاهرة التسرب النقدي خارج الجهاز المصرفي الع ا رقي، والتي اثرت سلباً على اجمالي الموارد وقوضت من القدرة التمويلية للمصارف مما يستدعي التفكير في المزيد من السبل والاج ا رءات لجذب المدخ ا رت الى الجهاز المصرفي الع ا رقي، وقد اعتمد البحث على المنهج الوصفي التحليلي في تحليل الجوانب الأساسية للنظام ، واظهرت نتائج البحث ان تطبيق نظام التأمين على الودائع من افضل السبل لتحقيق ذلك، وان النظام سوف يسهم في زيادة ثقة الجمهور الع ا رقي بالمصارف التجارية الع ا رقية ومن ضمنها المصارف الخاصة. مفاتيح البحث: نظام تأمين الودائع، اداء المصارف التجارية الع ا رقية، جذب الودائع. Abstract The research focused on the analysis of the impact of the establishment of deposit insurance scheme on the stability of the banking system through discussion and review of its features and its major issues, and the fact that Iraq's commercial banks and generally do not invest their deposits (though limited) effectively as it shows the presence of frozen funds not invested by the banks as the commercial banks, particularly private ones characterized by small size and inadequate for the granting of credit loans and advances to contribute to the economic development, and this is due to the sizes of depositors for deposit their savings in the Iraqi banking system so explained Find the reasons for this reluctance, and sought to identify the real causes that led to the reluctance of depositors for deposit their savings in government and private banks in areas where the branches of these banks, and the growing phenomenon of leakage of cash outside the Iraqi banking system, which impacted negatively on the total resources and undermined the financing capacity of the banks, which calls for thinking in more ways and measures to attract savings to the Iraqi banking system, has adopted a search on the descriptive approach analytical analysis of key aspects of the system, and the results showed that the application of the system of deposit insurance of the best ways to achieve this, and that the system will contribute to increased public confidence in the Iraqi commercial banks, including private banks. Keywords: Deposit insurance system, the performance of the Iraqi commercial banks, attract deposits.